The effects of a resistance-training program on strength, body composition and baseline hormones in male athletes training concurrently for rugby union 7`s - Crewther, B. T.; Heke, T. L.; Keogh, J. W. (The Journal of Sports Medicine and Physical Fitness, 2013)
Aim: To examine the effects of a resistance-training program on strength, body composition and baseline hormones in male athletes training concurrently for rugby union 7`s. Methods: Participants (N.=12) completed a six-week resistance-training program focusing on general strength development while still performing additional rugby union 7`s training involving agility, speed and cardiovascular fitness. One repetition maximum (1RM) strength was assessed pre and post training across 5 exercises (bench press, back squats, deadlifts, military press and chins), along with body composition and baseline salivary testosterone (T) and cortisol (C) concentrations. Results: Significant improvements in bench press (11%), back squat (13%), deadlift (13%), military press (10%) and chin-up (6%) 1RM strength were observed after training (P 0.05). Correlational analyses indicated that most of the individual changes in strength, body composition and hormones were not significantly related. Conclusion: The implementation of a resistance-training program in male athletes already training for rugby union 7`s led to all-round improvements in maximal dynamic strength even while they continued to perform other forms of rugby-specific training. These findings support the use of resistance exercise as a supplement to sport-specific training for improving the performance capacity of 7`s rugby players.